Tree-ring reconstruction of summer temperature for A.D. 1475–2003 in the central Hengduan Mountains, Northwestern Yunnan, China - Li, Zong-Shan; Zhang, Qi-Bin; Ma, Keping (Climatic change, 2012)
Development of long tree-ring records is an important task in paleoclimate studies. Here we presented a five-century long reconstruction of summer (June to August) temperature based on a tree ring-width chronology of Picea brachytyla var. complanata originating from the Hengduan Mountains of China. Climate-growth response analysis showed that summer temperature was the main climatic factor limiting tree-ring growth in the study area. The reconstructed summer temperature accounted for 47.6% of the variance in actual temperature during their common period A.D. 1958–2002. Analysis of the temperature reconstruction showed that major warm periods occurred in the A.D. 1710s–1750s, 1850s, 1920s–1950s and 1990s to present, whereas cold intervals occurred in the A.D. 1630s–1680s, 1790s–1800s, 1860s–1880s and 1950s–1980s, respectively. The low-frequency variation of the reconstruction agreed fairly well with tree-ring reconstructed temperature from nearby regions and with records of glacier fluctuations in the surrounding high mountains, suggesting that our reconstructed summer temperature was reliable, and could aid in the evaluation of regional climate variability.